The Role of Pakistani Media in Normalizing Conspiracy Theories: A Study of Communication Patterns and Audience Beliefs - Sara Anwar (Indus Journal of Social Sciences, 2025)
Now that the media has gone beyond the reach of the control of governments, the financiers, media organizations, and anchors are the ones who make heroes and antagonists, leaders and extremists. Pakistan, a developing country, which faces a lot of societal, fiscal, governmental, and safety issues, is as well not protected from the effects of the modern media. The Pakistani media is described to be open, candid and proactive nowadays as compared to the earlier days. Peer to peer news and discussions didn’t exist then, so most rely on the news and commentary provided by the state television for independent sources. Perfect for the media would be a situation where it gives objective information and is not influenced by propaganda. The people deserve to be given an understandable explanation. The exaggerated role of media has empowered media anchors with a lot of power whereby through political debate and populism through media, they are influencing policy making and they also wish to become decision makers. Evidence is building saying that there are constant personal differences in the predisposition to believing in conspiracy theories; Persons who subscribe to one conspiracy theory may tend to believe the others too. However, instruments measuring beliefs about specific conspiracy theories can be tightly connected to certain time and place. With these constraints in mind, it has been suggested that it is imperative to assess the overall inclination to entertain conspiracy theories without such assessment relying upon the cultural familiarity of specific theories.